To treat or not to treat: a state-of-the-art overview of smoldering multiple myeloma - Garg, Ayushi; Devarakonda, Srinivas (Frontiers in Hematology, 2026)
Smoldering multiple myeloma (SMM) is a plasma cell disorder characterized by an elevated monoclonal protein and increased bone marrow plasma cells (BMPC) without end-organ damage. It is an intermediate stage on the spectrum of plasma cell disorders, between monoclonal gammopathy of undetermined significance (MGUS) and symptomatic (active) multiple myeloma (MM). While most patients remain asymptomatic for years, a high-risk subset progresses rapidly. Traditional “watch-and-wait” strategy while avoiding toxicities associated with unnecessary therapy, can potentially delay treatment in those at increased risk for progression to MM associated with painful bone lesions, anemia, kidney failure and hypercalcemia. Hence, selection of the appropriate patient for treatment by accurate determination of individual risk of progression is vital in improving outcomes while avoiding toxicity. This review discusses the risk-stratification methods and evaluate various clinical therapeutic interventions for high-risk SMM, including immunomodulatory drugs, monoclonal antibodies, bispecific antibodies, and Chimeric Antigen Receptor- T cell (CAR-T) therapies along with their outcomes, safety profiles and limitations. We also discuss the importance of shared decision-making between clinicians and patients, tailoring monitoring and treatment to individual preferences to ensure that each patient receives maximum benefit and minimum harm.